Relacionamento sustentável: ações socioambientais como estratégia de marketing de relacionamento em canais de venda direta - Silva, Maria Erivanilda da (2018)
The present research has the general objective of verifying the use of social and environmental actions of beauty and personal hygiene products manufacturers organizations, as marketing strategy of relationship with their direct sales channels and, if positive, they generate loyalty. The methodology used counted on a bibliographical study, in order to grant a theoretical basis to the research. In addition, interviews were conducted with a semi-structured questionnaire, together with thirty-two exclusive and multi-brand resellers of Avon companies; Natura; The boticario; Hinode Group; as well as each of the four managers / reseller leaders from the relevant brand. It should be noted that these companies were chosen because they adopted recognized sustainability actions. The results show that there are differences in the perception of social and environmental actions by the resellers, according to the number of companies they represent. Exclusive resellers support the sustainable practices of the represented companies, and socio-environmental responsibility actions can further intensify their relationship with the brand they represent, although resellers consider other factors that together generate loyalty. Resellers who represent more than one brand support that companies are sustainable, but this does not make them brand loyal, since the greater interest is the financial gain.